Bargaining Models of Household Behavior: An Empirical Test Using the Luxembourg Income Study - Shelley Phipps; Peter Burton (Luxembourg Income Study (LIS), 1993)
Combines micro-data from seven LIS countries with macro/institutional variables (also provided by LIS) to test the implication of divorce-threat bargaining models of household behavior that 'extra-marital environmental parameters' should influence behavior.
Keywords: 330